Dynamics of fungal bioaerosols in Kuwait City: An 8-year survey - Abdullah AlSaleh; Mai Marafie; Hasan Dashti; Laila Ashkanani (PLoS ONE, 2025)
Fungi are ubiquitous eukaryotic microorganisms that are often implicated in a wide range of diseases. Exposure to fungal bioaerosols is often associated with conditions such as asthma, allergic rhinitis, keratitis, and pneumonitis, among others. This study aims to shed some light on the configuration of airborne culturable fungal genera in the atmosphere of Kuwait City with analysis of seasonal patterns, intra-diurnal variations and correlations with meteorological factors. Outdoor fungal bioaerosols samples were collected twice a day, two times a week, from January 2016 to December 2023 via volumetric active sampling in Al-Sabah Medical District, Kuwait City, Kuwait. The meteorological data were supplied by Kuwait Meteorological Department, Directorate General of Civil Aviation. The rates of fungal bioaerosols remained relatively high during the months of March, April and May, ranging from 269 to 296 CFU/m3. Cladosporium, Aspergillus and Alternaria were the most common fungal genera in the atmosphere, with a prevalence of 49%, 16% and 14%, respectively. Statistically significant differences (p < 0.05) in fungal composition between intra-diurnal periods were demonstrated in most monthly analyses. A strong negative correlation was demonstrated with temperature and haze events. Conversely, positive correlations were observed with relative humidity, wind action, rainfall and dust phenotypes. Fungal dynamics in relation to seasonality and intra-diurnal variations require further elucidation. Collaborative research is needed to advance our understanding of the implications of elevated rates of fungal bioaerosols, the seasonality of specific fungal allergens and what may be suitable means of mitigation. Efforts such as this study will hopefully help facilitate regionally specific air quality management decisions and provide baseline information for health-care providers.